2020
DOI: 10.1161/atvbaha.120.315214
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Mediated Regulation of Histone Demethylases Affects Angiogenesis-Associated Functions in Endothelial Cells

Abstract: Objective: Previous studies have demonstrated that the expression of several lysine (K)-specific demethylases (KDMs) is induced by hypoxia. Here, we sought to investigate the exact mechanisms underlying this regulation and its functional implications for endothelial cell function, such as angiogenesis. Approach and Results: We analyzed the expression changes of KDMs under hypoxia and modulation of HIF (hypoxia-inducible factor) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…It remains to be addressed, for example, whether KDM6A/B inhibition with GSK-J4 alters the microenvironment of solid tumours, including their stroma, vasculature and immune cell infiltration. Interestingly, Liu et al (2020) demonstrated an essential role for KDM6B-mediated H3K27 demethylation in the hypoxic induction of the gene encoding the pro-angiogenic mediator VEGFA [ 98 ]. Moreover, KDM6B knockdown or inhibition with GSK-J4 was found to inhibit endothelial cell proliferation and tube formation under hypoxic conditions [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be addressed, for example, whether KDM6A/B inhibition with GSK-J4 alters the microenvironment of solid tumours, including their stroma, vasculature and immune cell infiltration. Interestingly, Liu et al (2020) demonstrated an essential role for KDM6B-mediated H3K27 demethylation in the hypoxic induction of the gene encoding the pro-angiogenic mediator VEGFA [ 98 ]. Moreover, KDM6B knockdown or inhibition with GSK-J4 was found to inhibit endothelial cell proliferation and tube formation under hypoxic conditions [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…The so-called epigenetics refers to heritable phenotypic changes without those in DNA sequence [ 16 ]. In recent years, hypoxia-mediated epigenetic regulation has had a major function in the mechanism of OSAS [ 17 ]. Under chronic intermittent hypoxia-reoxygenation circumstances, the epigenetic process influences the adaptive potential and phenotypic variability, which contributes to the development of numerous deleterious effects of OSAS [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of microarrays and RNA sequencing is they only provide a measure of steady state RNA levels without any information on the relative contributions of RNA transcription and decay rates. Methods detecting nascent RNA, namely metabolic RNA pulse labelling sequencing, GRO-seq and precision run-on (PRO)-seq, have elucidated direct transcriptional changes in response to low oxygen [36,38,[42][43][44][45], and determined the relative contributions of transcription and decay to changes in mRNA levels [44]. These data find that transcription is the major contributor to changes in transcript levels in response to hypoxia and that these changes are mainly HIF dependent.…”
Section: The Use Of Transcriptomics Techniques In Hypoxiamentioning
confidence: 99%
“…ChIP-seq studies have shown hypoxia induces redistribution of the histone methylation landscape co-ordinating changes in hypoxia gene expression [ 40 , 61–64 ]. This work has contributed to the identification of specific JmjC histone demethylases, namely lysine demethylase 6A (KDM6A) and KDM5A, as oxygen sensors [ 62 , 64 ], determining the dependence of SET1B on H3K4me3 and gene expression changes in hypoxia [ 40 ], and elucidating the role of KDM4B and KDM6B in regulating hypoxic VEGFA expression and angiogenesis [ 43 ]. Furthermore, genome wide mapping of H3K27ac, a histone modification associated with transcriptionally active/poised genes, finds hypoxia induces changes in H3K27ac at gene loci correlating with effects of hypoxia on gene expression [ 42 ].…”
Section: Genomic Approaches Used In Hypoxia Researchmentioning
confidence: 99%